Medical educators’ perception of communication training with simulated patients: an explorative study approach - Alvarez, Simone; Schultz, Jobst-Hendrik (BMC Research Notes, 2017)
Medical students’ perceptions of the use of simulated patients (SP) in communication training in medicine have been studied intensively, but insights about faculty perception of this type of simulation training remain rare. This study aimed to assess medical educators’ perception of the relevancy of SP communication training, as well as its closeness to reality. Medical educators were surveyed by standardized questionnaire and open-ended questions. The questionnaire allowed educators to rate several aspects of the training such as its closeness to reality and relevancy to real-life physician-patient interaction.